2019
DOI: 10.17494/ogusbd.548291
|View full text |Cite
|
Sign up to set email alerts
|

Temel Eğitim Bölümünde Öğrenimlerini Sürdüren Öğretmen Adaylarının Öğretmenlik Mesleğine Yönelik Kaygı Düzeylerinin İncelenmesi

Abstract: Bu araştırmanın amacı Temel Eğitim Bölümü'nde öğrenimlerini sürdüren öğretmen adaylarının öğretmenlik mesleğine yönelik kaygılarını belirlemektedir. Araştırmada tarama modeli kullanılmıştır. Bu bağlamda 2017-2018 öğretim yılında Çanakkale Onsekiz Mart Üniversitesi Eğitim Fakültesi Temel Eğitim Bölümünde öğrenimlerini sürdüren öğretmen adayları araştırmanın evrenini oluşturmaktadır. Araştırmanın örneklemini ise amaçlı örnekleme türlerinden kolay ulaşılabilir durum örneklemesi ile belirlenen 741 öğretmen adayı o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…When the literature on professional anxiety of prospective teachers was examined, it was found that the professional anxiety of teacher candidates did not differ according to their gender (Abalı Öztürk et al, 2019;Atmaca, 2013;Bozdam & Taşkın, 2011;Dilmaç, 2010;Dinçer et al, 2015;Dursun & Karagün, 2012;Kafkas et al, 2010;Karademir & Tezel, 2011;Keskin, 2017;Ünaldı & Alaz, 2008); they had a low level of professional anxiety (Dilmaç, 2010;Doğan & Çoban, 2009;Kalemoğlu Varol et al, 2014;Köse, 2006) and moderate occupational anxiety (Bozdam & Taşkın, 2011;Keskin, 2017;Serin et al, 2015;Tabancalı et al, 2016); they had a high level of professional anxiety (Akgün & Özgür, 2014;Donmuş et al, 2007;Sezgin Nartgün & Gökçer, 2014); in all types of anxiety, the average of female teacher candidates was higher than that of men (Çakmak & Hevedanlı, 2005;Çubukçu & Dönmez, 2011;Kaya & Büyükkasap, 2005;Marso & Pigge, 1998;Tümerdem, 2007;Türkdoğan, 2014;Ünaldı & Alaz, 2008); that men's occupational anxiety was higher than women's (Akgün & Özgür, 2014;Donmuş et al, 2007); they had the idea that they would experience anxiety mostly in classroom management and least in communication with their colleagues (Çakmak, 2008); their anxiety levels decreased as their age increased (Bozdam & Taşkın, 2011); the age factor did not significantly affect anxiety levels statistically (Atmaca, 2013); professional concerns did not show any significant differentiation according to the type of high school they graduated from (Türkdoğan, 2014);...…”
Section: Professional Anxiety Towards Teaching Professionmentioning
confidence: 99%
“…When the literature on professional anxiety of prospective teachers was examined, it was found that the professional anxiety of teacher candidates did not differ according to their gender (Abalı Öztürk et al, 2019;Atmaca, 2013;Bozdam & Taşkın, 2011;Dilmaç, 2010;Dinçer et al, 2015;Dursun & Karagün, 2012;Kafkas et al, 2010;Karademir & Tezel, 2011;Keskin, 2017;Ünaldı & Alaz, 2008); they had a low level of professional anxiety (Dilmaç, 2010;Doğan & Çoban, 2009;Kalemoğlu Varol et al, 2014;Köse, 2006) and moderate occupational anxiety (Bozdam & Taşkın, 2011;Keskin, 2017;Serin et al, 2015;Tabancalı et al, 2016); they had a high level of professional anxiety (Akgün & Özgür, 2014;Donmuş et al, 2007;Sezgin Nartgün & Gökçer, 2014); in all types of anxiety, the average of female teacher candidates was higher than that of men (Çakmak & Hevedanlı, 2005;Çubukçu & Dönmez, 2011;Kaya & Büyükkasap, 2005;Marso & Pigge, 1998;Tümerdem, 2007;Türkdoğan, 2014;Ünaldı & Alaz, 2008); that men's occupational anxiety was higher than women's (Akgün & Özgür, 2014;Donmuş et al, 2007); they had the idea that they would experience anxiety mostly in classroom management and least in communication with their colleagues (Çakmak, 2008); their anxiety levels decreased as their age increased (Bozdam & Taşkın, 2011); the age factor did not significantly affect anxiety levels statistically (Atmaca, 2013); professional concerns did not show any significant differentiation according to the type of high school they graduated from (Türkdoğan, 2014);...…”
Section: Professional Anxiety Towards Teaching Professionmentioning
confidence: 99%